Chinese Commercial Audacity: Trade Conditions, Boycotts, and Legal Strife in Late Colonial Indonesia - Claver, Alexander (Paramita: Historical Studies Journal, 2023)
Towards the end of the nineteenth-century Chinese commercial penetration of colonial Java’s interior was held responsible for all economic and social wrongdoings. Chinese entrepreneurs responded to deteriorating sentiments and circumstances with increasing assertiveness towards the colonial government and/or its commercial establishment. Aware of their crucial economic position within the colony, they turned their organizational skills and aptitude in legal matters into the formidable weapon of trade boycotts. These boycotts are examples of a Chinese collective agency in which individual entrepreneurs pooled their knowledge, skills, and resources and acted in concert to shape their future. Chinese traders’ capacity to act forcefully in their given – unfriendly – environment undercuts the persistent tendency to objectify colonial actors excluded from political power. However, far from being passive and reacting objects, these entrepreneurs actively engaged (individually and collectively) with colonial (legal) power structures, displaying purposeful, goal-directed activity along the way. How to account for this uncharacteristically visible conduct? This paper seeks to answer the question by zooming in on the functions of trade in general and, second, late colonial conditions under which trade was conducted in the Netherlands Indies. It is argued that the Chinese trader’s room for manoeuvre stemmed from a unique combination of systemic functions and historical conditions. A combination that provided the Chinese trading community with the necessary (legal) loopholes to act upon enabled the transformation of collective agency into forceful trading boycotts.Keywords: commercial penetration, commercial audacity, Boycotts, Legal Strife, late colonial IndonesiaMenjelang akhir abad ke-19, penetrasi komersial Cina ke pedalaman Jawa kolonial dianggap bertanggung jawab atas semua kesalahan ekonomi dan sosial. Pengusaha Tionghoa menanggapi sentimen dan keadaan yang memburuk dengan meningkatkan ketegasan terhadap pemerintah kolonial dan/atau pendirian komersialnya. Sadar akan posisi ekonomi mereka yang penting di dalam koloni, mereka mengubah keterampilan organisasi dan bakat mereka dalam masalah hukum menjadi senjata boikot perdagangan yang tangguh. Boikot ini adalah contoh agen kolektif China di mana pengusaha individu mengumpulkan pengetahuan, keterampilan, dan sumber daya mereka dan bertindak bersama untuk membentuk masa depan mereka. Kapasitas para pedagang Cina untuk bertindak secara paksa dalam lingkungan mereka yang tidak ramah melemahkan kecenderungan yang terus-menerus untuk mengobjektifkan aktor-aktor kolonial yang dikucilkan dari kekuasaan politik. Namun, jauh dari objek yang pasif dan bereaksi, pengusaha ini secara aktif terlibat (secara individu dan kolektif) dengan struktur kekuasaan (hukum) kolonial, menampilkan aktivitas yang bertujuan dan diarahkan pada tujuan di sepanjang jalan. Bagaimana menjelaskan perilaku yang terlihat tidak seperti biasanya ini? Makalah ini berusaha menjawab pertanyaan tersebut dengan menyoroti fungsi perdagangan secara umum dan, kedua, kondisi kolonial akhir di mana perdagangan dilakukan di Hindia Belanda. Dikatakan bahwa ruang manuver trader China berasal dari kombinasi unik dari fungsi sistemik dan kondisi historis. Variasi yang memberi komunitas perdagangan Cina celah (hukum) yang diperlukan untuk bertindak memungkinkan transformasi agensi kolektif menjadi boikot perdagangan yang kuat.Kata kunci: penetrasi komersial, keberanian komersial, Boikot, Legal Strife, Indonesia kolonial akhir